2005
DOI: 10.1515/bc.2005.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional down-regulation of neurotrophin-3 in chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) leads to progressive development of airflow limitation and is characterised by cough, mucus hypersecretion and inflammatory changes. These characteristic features of the disease may be modulated by neural mediators such as neurotrophins (NT). Here we examined the expression and transcriptional regulation of neurotrophins in bronchial biopsies of COPD patients and compared the data to control biopsies. Histology revealed characteristic changes in the COPD tissues, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…A marked down‐regulation of NT‐3 mRNA expression and constant levels of NGF, BDNF, and NT‐4/5 mRNA expression were shown. Together with the present data on p75NTR, these data on neurotrophin‐specific transcriptional down‐regulation of NT‐3 in human COPD indicate that there may be disease‐ and cell type‐specific differences in the regulation of the expression of neurotrophins and their receptors [27]. Changes observed may therefore not present an epiphenomenon of the inflammatory processes but could be considered to be disease‐specific and related to the microenvironment.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A marked down‐regulation of NT‐3 mRNA expression and constant levels of NGF, BDNF, and NT‐4/5 mRNA expression were shown. Together with the present data on p75NTR, these data on neurotrophin‐specific transcriptional down‐regulation of NT‐3 in human COPD indicate that there may be disease‐ and cell type‐specific differences in the regulation of the expression of neurotrophins and their receptors [27]. Changes observed may therefore not present an epiphenomenon of the inflammatory processes but could be considered to be disease‐specific and related to the microenvironment.…”
Section: Discussionsupporting
confidence: 57%
“…This ligand may also play a role in chronic inflammatory diseases and only a limited number of studies assessed the regulation of this p75NTR ligand in chronic inflammation. Whereas NGF seems to be induced under the state of chronic inflammation, a recent study pointed to a potential down‐regulation of NT‐3 in chronic inflammatory diseases such as chronic obstructive pulmonary disease (COPD) [27]. For this disease that is currently the fourth most common cause of death in the world, real‐time PCR studies revealed a differential mRNA expression of neurotrophins.…”
Section: Discussionmentioning
confidence: 99%
“…A differential regulation for NTs with a reduction vs. induction of different molecules has so far only been demonstrated for a limited number of pathological states [32]. By combining the data of the present and previous studies, it can be concluded that the NT system does not act uniformly with an up-regulation of gene expression towards any inflammatory stimulus as shown, i.e.…”
Section: Bdnf M a R K E R H 2 O M A S T C E L L S K E R A T I N O C Ysupporting
confidence: 56%
“…Since there are no data available on the expression of this important cytokine signal inhibitor in COPD, the aim of the present study was to address the transcriptional expression level of SOCS-3 along with SOCS-4 and SOCS-5 in bronchial tissues of a previously characterized cohort of COPD patients [12,22]. …”
Section: Introductionmentioning
confidence: 99%